2010
DOI: 10.1093/aje/kwq155
|View full text |Cite
|
Sign up to set email alerts
|

Leisure Time Spent Sitting in Relation to Total Mortality in a Prospective Cohort of US Adults

Abstract: The obesity epidemic is attributed in part to reduced physical activity. Evidence supports that reducing time spent sitting, regardless of activity, may improve the metabolic consequences of obesity. Analyses were conducted in a large prospective study of US adults enrolled by the American Cancer Society to examine leisure time spent sitting and physical activity in relation to mortality. Time spent sitting and physical activity were queried by questionnaire on 53,440 men and 69,776 women who were disease free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

23
364
3
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 521 publications
(409 citation statements)
references
References 48 publications
(52 reference statements)
23
364
3
9
Order By: Relevance
“…One explanation for this lack of an association may be that, in the context of other risk factors for these conditions, the risk attributable to sedentary behaviour is relatively small. This is supported by studies that examined associations between sitting and all-cause mortality in middle-aged women, which found statistically significant but small adjusted hazard ratios [HRs] (HR=1.10 29 and HR=1.34 30 for the highest level of sitting).…”
Section: Discussionmentioning
confidence: 72%
“…One explanation for this lack of an association may be that, in the context of other risk factors for these conditions, the risk attributable to sedentary behaviour is relatively small. This is supported by studies that examined associations between sitting and all-cause mortality in middle-aged women, which found statistically significant but small adjusted hazard ratios [HRs] (HR=1.10 29 and HR=1.34 30 for the highest level of sitting).…”
Section: Discussionmentioning
confidence: 72%
“…In line with another study, we did not find a significant effect of physical activity on cancer mortality in women (Table 3) . However, a study reported significant effects in women but not in men (Patel et al, 2010). Because the strongest evidence for a protective effectbesides for colon cancer -is available for breast cancer (Physical Activity Guidelines Advisory Committee, 2008), stronger associations in women could be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Independent of moderate-to vigorous-intensity physical activity (MVPA), sedentary behavior, defined as activities between 1.0 and 1.5 metabolic equivalents, is associated with increased risk of disability [1] and premature mortality [2]. Prolonged sedentary time is also linked with numerous health conditions, including cardiovascular disease [3,4], metabolic syndrome [5,6], obesity [7], and breast cancer [8].…”
Section: Introductionmentioning
confidence: 99%